Frequent Antiviral Treatment Failures in Patients Infected With Hepatitis C Virus Genotype 4, Subtype 4r. Issue 2 (5th January 2019) - Fourati, Slim; Rodriguez, Christophe; Hézode, Christophe; Soulier, Alexandre; Ruiz, Isaac; Poiteau, Lila; Chevaliez, Stéphane; Pawlotsky, Jean‐Michel
Abstract : Hepatitis C virus (HCV) genotype 4 is highly heterogeneous. HCV subtype 4r has been suggested to be less responsive to direct‐acting antiviral (DAA) drug treatment than other genotype 4 subtypes. Among 537 DAA‐treated patients who experienced a virological failure (VF) in France between 2015 and 2018, 121 (22.5%) were infected with genotype 4 and 27 of them (22.3%) with subtype 4r; subtype 4r was thus over‐represented as compared to its prevalence in the French general population. Population sequencing of the nonstructural protein (NS) 3, NS5A, and NS5B genes was performed in all subtype 4r patients at treatment failure and in 6 at baseline, whereas full‐length HCV genome sequencing was performed in two baseline and three treatment failure samples by means of an original shotgun metagenomics method based on deep sequencing. At treatment failure, all subtype 4r patients harbored two to three dominant NS5A resistance‐associated substitutions (RASs), including at least L28A/C/I/M/V and L30R. Among 13 patients exposed to sofosbuvir and an NS5A inhibitor (daclatasvir, ledipasvir, or velpatasvir), 5 (38.5%) also harbored NS5B S282C/T RASs at treatment failure. An additional patient harbored S282C/T RASs at treatment failure by deep sequencing. Prevalence of S282C/T RASs at treatment failure was significantly higher in patients infected with genotype 4r than with other genotypes, including other subtypes of genotype 4. Conclusion : The lower rates of sustained virological response in patients infected with subtype 4r are related to the frequent preexistence at treatment baseline and subsequent selection by DAA treatment of both NS5A and NS5B S282 RASs. Our study suggests that these patients should be identified and receive a triple DAA combination regimen as first‐line treatment.